2013
DOI: 10.1177/0898264313482488
|View full text |Cite
|
Sign up to set email alerts
|

Serum Folate and B12 Levels in Association With Cognitive Impairment Among Seniors

Abstract: Low folate levels are associated with cognitive impairment of seniors; underlying pathophysiological mechanisms should be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 55 publications
3
24
2
6
Order By: Relevance
“…Additionally, the score in one of these studies (Penninx et al, 2000) was further reduced to 5/8, given that the sample comprised of physically disabled women, thus threatening representativeness and potentially causing a risk of selection bias. By contrast, five studies (Kim et al, 2008;Michelakos et al, 2013;Ng et al, 2009;Ramos et al, 2004;Tiemeier et al, 2002;) scored a perfect 8/8. Lastly, one-included cohort study (Kim et al, 2008) was evaluated as a cross-sectional study, given that only the baseline data were included in the meta-analysis.…”
Section: Eligible Studiesmentioning
confidence: 83%
See 4 more Smart Citations
“…Additionally, the score in one of these studies (Penninx et al, 2000) was further reduced to 5/8, given that the sample comprised of physically disabled women, thus threatening representativeness and potentially causing a risk of selection bias. By contrast, five studies (Kim et al, 2008;Michelakos et al, 2013;Ng et al, 2009;Ramos et al, 2004;Tiemeier et al, 2002;) scored a perfect 8/8. Lastly, one-included cohort study (Kim et al, 2008) was evaluated as a cross-sectional study, given that only the baseline data were included in the meta-analysis.…”
Section: Eligible Studiesmentioning
confidence: 83%
“…Lastly, it has recently been suggested that the L-methylfolate formation of folate may be more bioavailable as it enters the one carbon cycle after the step where MTHFR is needed; therefore, it should be administered instead of folic acid, especially in patients with this genetic variation as well as in those taking specific other medication or consuming alcohol. Interestingly, a previous meta-analysis from our group on the role of potential supplementation of the older age people also highlighted the sizeable role of low folate levels in affecting late-life cognitive function (Michelakos et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations